Abiotic stress tolerance-progress and pathways of sustainable rice production - Dar, Manzoor H.; Bano, Dilruba A.; Waza, Showkat A.; Zaidi, Najam W.; Majid, Asma; Shikari, Asif B.; Ahangar, M. Ashraf; Hossain, Mosharaf; Kumar, Arvind; Singh, Uma S. (MDPI, 2021)
Rice is globally a major food crop and its production has progressively been affected by various types of abiotic stresses especially drought, flooding, salinity, heat and cold in most of the cultivable rice ecosystems. The incidence, intensity and duration of these stresses are anticipated to aggravate due to climate change consequences, demanding resilient yields in these situations to be essential. Present paper deals with reviewing various types of abiotic stresses and their mitigation strategies for enhancing and stabilizing rice production in stress prone areas. Review of available literature pertaining to the study area has been used as research methodology for this paper. The available literature suggests that stress-tolerant varieties can serve as the most viable strategy to contribute in coping with the problem of abiotic stresses. Although, good progress has been made in the development of stress-tolerant rice varieties (STRVs) and incessant efforts are being made to spread these varieties in target areas, adoption by farmers is yet to meet expectations. Advantage, affordability, awareness and availability are the main factors responsible for adopting of any technology. The adoption of stress-tolerant varieties has not reached its potential, predominantly due to the lack of awareness and non-availability of seeds amongst farmers. Strategic and intentional collaborations should be ensured for scaling the sustainable delivery and diffusion of STRVs. A promotional roadmap that ensures the linkages between private and public seed sectors remains the key factor for its successful adoption. Similarly, strengthening of formal, informal and semi-formal seed systems is crucial to accelerate the dissemination of these varieties. There is an imperative need to create strategic plans for the development of varieties possessing multiple stress tolerance. Significant investments for sustainability of rice production in stress prone areas form the essential component of long-term agricultural development. The sooner these investments and strategies are accomplished, the greater the gains are expected.